A history of the Crusades - Setton, Kenneth M. 1914-1995 (University of Wisconsin Press, 1969)
The six volumes of A History of the Crusades will stand as the definitive history of the Crusades, spanning five centuries, encompassing Jewish, Moslem, and Christian perspectives, and containing a wealth of information and analysis of the history, politics, economics, and culture of the medieval world.